ELIMINATION OF SAFETY RISKS IN BIOGAS FACILITIES - GADUS, Jan; HASKOVA, Alena (Journal of Technology and Information Education, 2012)
Currently in the frame of utilization of various forms of renewable energy sources an important support is given to spreading biogas facility operation. These facilities contribute significantly to the environment protection and partly to energy independence of the country. However their operation is connected with some safety risks which are often underestimated in practice. Biogas facilities belong to restricted facilities, what means that their operation must be in line with relevant requirements regarding to explosiveness of the environment, noise, vibrations etc. The contribution pays attention to various aspects of their safety operation.
Keywords: biogas station; safety risks; operation safety; threat zones; occupational health and safety (OHS); meeting the safety rules; work safety management; Biomass Utilization Action Plan in Slovakia for the period 2008 - 2013